Neural responses to advantageous and disadvantageous inequity - Fliessbach, Klaus; Phillipps, Courtney B.; Trautner, Peter; Schnabel, Marieke; Elger, Christian E.; Falk, Armin; Weber, Bernd (Frontiers in Human Neuroscience, 2012)
In this paper we study neural responses to inequitable distributions of rewards despite equal performance. We specifically focus on differences between advantageous inequity (AI) and disadvantageous inequity (DI). AI and DI were realized in a hyperscanning functional magnetic resonance imaging (fMRI) experiment with pairs of subjects simultaneously performing a task in adjacent scanners and observing both subjects' rewards. Results showed (1) hypoactivation of the ventral striatum (VS) under DI but not under AI; (2) inequity induced activation of the right dorsolateral prefrontal cortex (DLPFC) that was stronger under DI than under AI; (3) correlations between subjective evaluations of AI evaluation and bilateral ventrolateral prefrontal and left insular activity. Our study provides neurophysiological evidence for different cognitive processes that occur when exposed to DI and AI, respectively. One possible interpretation is that any form of inequity represents a norm violation, but that important differences between AI and DI emerge from an asymmetric involvement of status concerns.